(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
CNC routers play a significant role in several markets such as furniture design, circuit board manufacturing, plastic and foam fabrication. It can allow to complete projects in few hours that used to take several days CNC routers can work on sheets of woods, plastic, rubber, acrylics, and non-ferrous metal and CNC router machine moves and cuts in three directions using computer aided design software. A computer program has been established to design the power screws of any engraving machine. The power required to cut material was calculated by the program. The resisting force was analyzed and all stresses act on the power screws. The power screws were designed by using the main common theory of failures. The buckling and maximum deflection was checked in this program. An example of the output results was designed and drawn in Advanced Centre of Technology using solid works software. The nut connected to the screws was also drawn. The parts of engraving machine have been manufactured and tested in Advanced Centre Technology A.C.T in Libya.